Art Bahrain- 05 S/S 2015 : 56th International Art Exhibition- La Biennale di Venezia 2015- Official Collateral Event - Al Afriji, Sadik; Al Khalifa, Rashid; Amin, Shurooq; El Shaer, Ahmed; Farhat, Simeen; Hafez, Khaled; Nawar, Haytham; Obaidi (2015)
Contemporary Practices Art Journal Pavilion.#NPUAE #SAFmedia
English
Keywords: Collateral event catalog; N4390-5098 Visual Arts- Exhibitions; Bahrain